Towards a modular language curriculum for using tasks. (July 2019) - Ellis, Rod
Task-based language teaching (TBLT) and task-supported language teaching (TSLT) are often seen as incompatible as they draw on different theories of language learning and language teaching. The position adopted in this article, however, is that both approaches are needed especially in instructional contexts where 'pure' task-based teaching may be problematic for various reasons. The article makes a case for a modular curriculum consisting of separate (i.e. non-integrated) task-based and structure-based components. Different curriculum models are considered in the light of what is known about how a second language is learned. The model that is proposed assumes the importance of developing fluency first. It consists of a primary task-based module implemented with focus-on-form (Long, 1991) and, once a basic fluency has been achieved, supported by a secondary structural module to provide for explicit accuracy-oriented work to counteract learned selective attention (N. Ellis, 2006): one of the main sources of persistent error. The article also addresses the content and grading of the task-based and structural modules. It considers the factors that need to be considered in the vertical and horizontal grading of tasks but also points out that, for the time being, syllabus designers will have to draw on their experience and intuition as much as on research to make decisions about how to sequence tasks. An argument is presented for treating the structural component as a checklist rather than as a syllabus so as to allow teachers to address selectively those features that are found to be problematic for their students when they perform tasks.